Classical Islamic Education Socio-Historical Analysis of Curriculum and its Relevance in the Contemporary Era - Ismail, Ismail (Edusia: Jurnal Ilmiah Pendidikan Asia, 2024)
The objective of the study is to evaluates the relevance of Islamic education methods in the classical era compared to the contemporary era. This study is a qualitative research, to analyze various phenomena in the form of literary facts and social facts related to classical and contemporary Islamic education. This research uses a literature study approach so that the data used is secondary data taken from document studies, reference books and academic journals that are relevant to the topic under study. This studi found that in general, the classical Islamic education curriculum is divided into two parts, namely the pre-madrasah curriculum and the post-madrasah curriculum. Although it has passed its golden age for centuries, the classical Islamic education curriculum remains relevant to contemporary education. One of its relevance lies in the foundation laid by classical Islamic education in developing critical and analytical thinking. Contemporary education also emphasizes the development of critical and analytical skills to answer the challenges of the modern era.